Development of electronic student worksheets using a Liveworksheet on Pythagorean theorem material class VIII junior high school - Ainun Krisna Devi; Sumargiyani Sumargiyani; Nur Robiah Nofikusumawati Peni; Samah Gamal Ahmed Elbehary (Universitas Sarjanawiyata Tamansiswa, 2023)
This research is inspired by the many students who think of mathematics as a difficult subject, one of which is the Pythagorean theorem. This study aimed to determine the validity and practicality of using the Electronic Student Worksheets or E-LKPD with a Liveworksheet on Pythagorean Theorem material. This type of research is research and development using the ADDIE development model. The subjects in this study were material experts, media experts, and class VIII A students of SMP Muhammadiyah Imogori. The findings show that the developed E-LKPD received a